Influence of purple basil (Ocimum basilicum L.) extract and essential oil on hyperlipidemia and oxidative stress in rats fed high-cholesterol diet - Gokce, Y.; Kanmaz, H.; Er, B.; Şahin, Kazım; Hayaloglu, A. A. (Elsevier, 2021)
The aim of this study was to investigate and compare the effects of purple basil methanolic extract and essential oil on serum lipid profiles in rats fed a high cholesterol diet. Feeding a high-cholesterol diet increased serum lipid profiles, leptin, hepatic triglyceride, cholesterol levels, malondialdehyde concentrations, fatty acid synthase (FAS), liver X receptors (LXRs), ATP-citrate lyase (ACLY), and sterol regulatory element-binding proteins (SREBP-1c) expression in the liver in rats. The extract and essential oil reduced serum triglycerides by 28.2%, 30.7%, and total cholesterol by 21.7% and 14.5%, respectively. The applications did not return the aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities to their normal levels. Extract and feno-fibrate administration decreased serum leptin levels by 17.5% and 27.5%, respectively. The extract reduced hepatic triglyceride by 16.4% and total cholesterol by 22.1%. Fenofibrate reduced the triglyceride and hepatic total cholesterol by 25.5% and 46.3%, respectively. The decrease in MDA levels was 34.6% in those treated with the extract, and less in those who were applied essential oil. Expression of fatty acid synthase (FAS), liver X receptors (LXRs), ATP-citrate lyase (ACLY), and sterol regulatory element-binding proteins (SREBP-1c) in the liver decreased by 20.9%, 15.4%, 20.7% and 16.9%, respectively, when the extract was administered. For those treated with essential oil, the decline was 9.9%, 13.6%, 10.2%, and 12.5%. It decreased by 38.1%, 56.8%, 21.7% and 40.8% in those administered fenofibrate. The ABTS and DPPH based antioxidant activities and total phenolic contents of the extract were 67.83%, 86.98% and 57.94 +/- 0.39 mg Gallic acid equivalent (GAE), respectively. The results reveal that methanolic extract of purple basil may contain hypolipidemic and antioxidant substances and its protective effect on the liver.
Keywords: Ocimum basilicum L.; Hypolipidemia; High cholesterol; Antioxidant activity; Essential oil